2011
DOI: 10.3748/wjg.v17.i16.2076
|View full text |Cite
|
Sign up to set email alerts
|

A practical approach to the diagnosis of autoimmune pancreatitis

Abstract: Autoimmune pancreatitis is a disease characterized by specific pathological features, different from those of other forms of pancreatitis, that responds dramatically to steroid therapy. The pancreatic parenchyma may be diffusely or focally involved with the possibility of a low-density mass being present at imaging, mimicking pancreatic cancer. Clinically, the most relevant problems lie in the diagnosis of autoimmune pancreatitis and in distinguishing autoimmune pancreatitis from pancreatic cancer. Since in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 43 publications
1
19
0
1
Order By: Relevance
“…Recent histological and clinical studies have suggested the existence of 2 subtypes of AIP: type 1 AIP related to IgG4 exhibiting LPSP, and type 2 AIP related to GELs exhibiting IDCP (10,11). Both types share some representative pathology, such as pancreatic enlargement, narrowing of the MPD, lymphoplasmacytic infiltration with fibrosis in the pancreas, and dramatic response to steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent histological and clinical studies have suggested the existence of 2 subtypes of AIP: type 1 AIP related to IgG4 exhibiting LPSP, and type 2 AIP related to GELs exhibiting IDCP (10,11). Both types share some representative pathology, such as pancreatic enlargement, narrowing of the MPD, lymphoplasmacytic infiltration with fibrosis in the pancreas, and dramatic response to steroids.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to LPSP, patients with IDCP have no serological markers of autoimmunity, and IDCP is occasionally associated with inflammatory bowel diseases such as ulcerative colitis or Crohn's disease (7). Recently, the clinical profiles of LPSP and IDCP have begun to be referred to as "type 1" and "type 2" AIP, respectively (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In our case, AIP was diagnosed based on the criteria established by the Japan Pancreas Society [2,11] . AIP presentation has recently been divided into either subtype type 1 or 2 [12][13][14] . In Asia, type 1 AIP presents at a higher frequency and is also referred to as lymphoplasmacytic sclerosing pancreatitis or AIP without granulocyte epithelial lesions (GELs).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Japanese and Asian consensus criteria (imaging of pancreatic parenchyma and duct appearance, elevated serum IgG4/autoantibodies, LPSP with IgG4-positive plasma cells) [ 26 , 27 ] or the American HISORt criteria (histology showing LPSP/IDCP, suggestive imaging, elevated serum IgG4, other organ involvement, response to steroids) [ 15 ], the Italian criteria do not consider serological changes as diagnostic, refl ecting the high prevalence of IgG4-negative AIP type 2 among their study cohort. They emphasize the importance of a steroid response as proof of diagnosis, when clinically justifi ed and also suggested that of the following four criteria, three had to be fulfi lled to allow the diagnosis of AIP [ 28 ] The diagnostic work-up that used these Italian criteria initially distinguished between diffuse "sausage-shaped" swelling of the pancreas and a focal, hypodense mass that mimics malignancy [ 29 ]. In cases of diffuse swelling, acute pancreatitis was considered the principal differential diagnosis, which can be easily ruled out by the absence of elevated serum pancreatic enzyme activity, absence of pancreatic necrosis, and only mild abdominal symptoms.…”
Section: Diagnostic Approachesmentioning
confidence: 99%